Real options theory - Reuer, J. J.; Tong, Tony W. (Emerald, 2007)
Real options theory has attracted significant interest in the field of strategic management. Advocates of the approach emphasize that importing concepts from financial economics holds out the potential of yielding new insights on strategic decision-making under uncertainty as well as boundary-of-the-firm issues that are the focus of competitive and corporate strategy. While considerable progress has been made in conceptualizing different types of real options for various strategic investments, considerably less has been done to empirically validate the core propositions of real options theory. As a result there is much debate about the merits and promise of real options in strategy.In light of the recent interest in real options as well as these trends in the field, this volume examines the ways in which real options theory can contribute to strategic management. This volume offers conceptual pieces that trace out pathways for the theory to move forward and presents new research on the implications of real options for strategic investment, organization, and firm performance. The compendium synthesizes and critiques the research on real options as well as offers a catalyst for further research on this theory in the strategy field. It seeks to examine the ways in which real options theory can contribute to strategic management. It includes conceptual pieces that unearth some of the key stumbling blocks and trace out pathways for real options theory to move forward. It presents theoretical and empirical analyses of real options in different strategic contexts.
Keywords: Strategic planning.; elektronické knihy; electronic books